Financial Performance of Hospital Telehealth Adopters, Nonadopters, and Switchers: A Rural-Urban Comparison - Karim, Saleema A.; Bogulski, Cari A.; Tilford, J. Mick; Hayes, Corey J.; Eswaran, Hari (Journal of healthcare management, 2025)
Goals: The adoption of telehealth in healthcare delivery has transformed patient treatment options. Urban and rural hospitals are increasingly using telehealth to reach more patients, improve patient engagement, and increase healthcare quality. Hospitals experience the operational benefits of adopting telehealth through improving clinical workflow, increasing efficiency, and improving patient satisfaction. These benefits may have financial implications through increases in patient volume and revenue, and reductions in provider overhead and costs. The overall effect of telehealth adoption on hospital financial performance is currently unknown. This study examines the association of telehealth adoption with the financial performance of rural and urban hospitals. Methods: This study uses retrospective data to examine the differences between urban and rural hospitals and community characteristics, profitability, and telehealth adoption from 2009 to 2019 in the United States. Data were obtained from the American Hospital Association Annual Survey and the Information Technology Supplement, the Centers for Medicare & Medicaid Services Healthcare Cost Report Information Systems, and the Area Health Resource File. Telehealth adoption status was determined using the American Hospital Association Annual Survey and the Information Technology Supplement Survey. Hospitals were classified into three categories, according to telehealth adoption status: (1) telehealth persistent nonadopters, (2) telehealth persistent adopters, and (3) telehealth switchers. Hospital financial performance was measured using operating margin and total margin. Descriptive statistics were used to evaluate the variation between the three categories of telehealth adoption status and hospital characteristics, hospital financial performance, and community characteristics. Principal Findings: The study sample of 1,530 hospitals consisted of 56% rural hospitals and 44% urban hospitals. The results reveal disparities in financial performance between rural and urban hospitals. From 2009 to 2019, both rural and urban hospitals, identified as telehealth persistent adopters, exhibited higher operating and total margins compared to telehealth persistent nonadopter hospitals. Hospitals that transitioned from telehealth nonadopters to telehealth adopters, started with operating and total margins that closely aligned with telehealth persistent nonadopters. However, as hospitals adopted telehealth, both operating and total margins followed closely to telehealth persistent adopters. The results indicate that while hospital financial performance is associated with telehealth adoption, inferring causation is beyond the scope of these results. Practical Applications: The telehealth adoption status has unveiled noticeable patterns in hospital financial performance. In both rural and urban settings, hospitals persistently lacking telehealth capacity have the worst financial performance when compared to hospitals that persistently maintained telehealth services or hospitals that adopted telehealth over the study period. Overall, urban hospitals had better financial performance, which is likely associated with higher caseloads and payer mix compared to rural hospitals. Hospitals that adopted telehealth over the study period showed an increase in financial margins similar to hospitals with persistent telehealth adoption. Targeted policies that address the specific financial challenges of hospitals with a history of poor performance could effectively increase telehealth adoption in these settings. Future research should examine whether adoption among hospitals persistently lacking telehealth can influence the quality and accessibility of services, along with associated health outcomes to determine whether more aggressive policy action is warranted.